What “Price” Means When Buying Food: Insights From a Multisite Qualitative Study With Black Americans - DiSantis, Katherine Isselmann (American Public Health Association, 2013)
Objectives. We explored the role of price in the food purchasing patterns of Black adults and youths. Methods. We analyzed qualitative data from interviews and focus groups with socioeconomically diverse, primarily female, Black adults or parents (n = 75) and youths (n = 42) in 4 US cities. Interview protocols were locality specific, but all were designed to elicit broad discussion of food marketing variables. We performed a conventional qualitative content analysis by coding and analyzing data from each site to identify common salient themes. Results. Price emerged as a primary influence on food purchases across all sites. Other value considerations (e.g., convenience, food quality, healthfulness of product, and family preferences) were discussed, providing a more complex picture of how participants considered the price of a product. Conclusions. Food pricing strategies that encourage consumption of healthful foods may have high relevance for Black persons across income or education levels. Accounting for how price intersects with other value considerations may improve the effectiveness of these strategies.